EFEKTIVITAS ANTIOKSIDAN PADA SISTEM EMULSI MAYONES - Fatimah, Feti (Jurnal Entropi, 2009)
Mayonnaise represent the system of emulsion of oil-in-water, where oil rate is 50-85%. Height of oil rate of mayonnaise causes of the oxidation reaction more easy. The aims of this research where to study the effectiveness of antioxidant on its system. The effectiveness of antioxidant in the system attributed by its polarity. The polarity of antioxidant was measured by determining of partition coefficient in octanol-water system (1:1). The effectiveness of antioxidants in the system were determined by Rancimat. Result of this research indicate that third type of antioxidants have the different polarity. The partition coefficient of butylated hydroxyl toluene (BHT) was 91%, t-butylhydroquinone (TBHQ) was 79.9%, and trollox was 0.47 (32.0%). From the Test of Rancimat known that the most effective type of antioxidants was TBHQ.